Human Touch Experience: A Strategy for Reducing Consumer Switching Behavior in The Financial Service Industry - Anton Dwi Fitriyanto; Mulyono Mulyono (Australasian Accounting, Business and Finance Journal, 2023)
This research provides an in-depth exploration of the Human Touch Experience (HTE) as a strategy for reducing consumer switching behavior in the financial service industry (Non-Bank). Amidst increasing competition and digitalization, maintaining customer loyalty has become a significant challenge for the industry. The study employed a mixed-methods approach, combining quantitative survey data from 1,207 respondents with qualitative data from 30 in-depth interviews. The findings underscore that high levels of HTE are associated with increased customer satisfaction and loyalty and a decreased intention to switch service providers. Furthermore, financial institutions that incorporate HTE practices into their operations report lower rates of customer churn and higher customer satisfaction and loyalty. The results suggest that, despite the digital revolution, a balance between efficient digital services and personalized human interaction can enhance customer relationships.
Keywords: Human Touch Experience; Consumer Switching Behavior; Financial Service Industry; Customer Satisfaction; Customer Loyalty